2021
DOI: 10.1108/ijshe-06-2020-0202
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service English language teachers’ conceptions of sustainable development: a case from Turkish higher education context

Abstract: Purpose The purpose of this paper is to explore how sustainable development (SD) is conceptualized by pre-service English language teachers in Turkey and design a specialized course syllabus on SD in English language teaching (ELT) in the light of the research findings. Design/methodology/approach The study used a mixed-methods sequential explanatory study design and investigated the case of a state university in Turkey with the involvement of 133 pre-service English language teachers. Findings The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The current studies showed that there were some attempts in implementing SDGs in education; however, it is far away from developing students' awareness on sustainable development [1][2][3]. First, most of the studies [4,5,14,[27][28][29][30][31] were posited on the implementation in SDGs at higher education level by analysing the relevancy of the course contents to the SDGs. A very few focussed on implementing SDGs in K-12 education [8][9][10][11][12][13][15][16][17][18]32].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The current studies showed that there were some attempts in implementing SDGs in education; however, it is far away from developing students' awareness on sustainable development [1][2][3]. First, most of the studies [4,5,14,[27][28][29][30][31] were posited on the implementation in SDGs at higher education level by analysing the relevancy of the course contents to the SDGs. A very few focussed on implementing SDGs in K-12 education [8][9][10][11][12][13][15][16][17][18]32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 1 summaries the challenges of implementing ESD in K-12 education. First, scholars [9][10][11][12]14,18] suggested that teachers' values and beliefs negatively influence their perception of ESD, which was reflected in their lack of interest in implementing sustainable development in their teaching. For instance, teachers felt that sustainability was a complicated concept with various definitions, and the interconnection between different aspects of sustainable development was hard to understand [18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations